Transkribiranje v sociolingvističnih raziskavah in korpusih govorjene slovenščine: Maja Bitenc - Krajnc Ivič, Mira (Stanje in perspektive uporabe govornih virov v raziskavah govora, 2024)
Transcription in Sociolinguistic Research and Corpora of Spoken Slovene. The article discusses transcription as a complex, interpretive, and selective process in which the transformation of spoken into written text raises numerous fundamental and practical questions. There are no standard transcription principles in sociolinguistic research; they always depend on the researcher's theoretical orientation, subject matter, and research purpose. The introductory part of the article presents theoretical considerations and general guidelines, while the central part focuses on various transcription practices in corpora and studies of spoken Slovene. Particular attention is paid to the notation of the variants of the /v/ phoneme, the semi-vowel, specific dialectal sounds and changes in sonority. Among other things, various transcription practices in the author's sociolinguistic studies of variation in spoken Slovene and relevant socio-psychological topics are described, ranging from initial precise phonetic transcriptions through various levels of simplification to the transition to orthographic representation with special symbols for individual sounds. The article also highlights challenges in distinguishing individual sounds and inconsistencies in their representation.